AXL Receptor Tyrosine Kinase as a Therapeutic Target in Hematological Malignancies: Focus on Multiple Myeloma - Yan, Siyang (Cancers (Basel), 2019)
AXL belongs to the TAM (TYRO3, AXL, and MERTK) receptor family, a unique subfamily of the receptor tyrosine kinases. Their common ligand is growth arrest-specific protein 6 (GAS6). The GAS6/TAM signaling pathway regulates many important cell processes and plays an essential role in immunity, hemostasis, and erythropoiesis. In cancer, AXL overexpression and activation has been associated with cell proliferation, chemotherapy resistance, tumor angiogenesis, invasion, and metastasis; and has been correlated with a poor prognosis. In hematological malignancies, the expression and function of AXL is highly diverse, not only between the different tumor types but also in the surrounding tumor microenvironment. Most research and clinical evidence has been provided for AXL inhibitors in acute myeloid leukemia. However, recent studies also revealed an important role of AXL in lymphoid leukemia, lymphoma, and multiple myeloma. In this review, we summarize the basic functions of AXL in various cell types and the role of AXL in different hematological cancers, with a focus on AXL in the dormancy of multiple myeloma. In addition, we provide an update on the most promising AXL inhibitors currently in preclinical/clinical evaluation and discuss future perspectives in this emerging field.